2004
DOI: 10.1007/s15010-004-3042-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Erythema Migrans Caused by Borrelia afzelii and Borrelia garinii

Abstract: Early localized Lyme borreliosis caused by B. afzelii and B. garinii has distinct epidemiological and clinical characteristics. Clinical features of EM depend upon the genospecies of Borrelia burgdorferi sensu lato causing the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 17 publications
7
49
0
1
Order By: Relevance
“…In the present study the frequency of systemic symptoms was less than reported in the USA, but was similar to other European studies (8,24 infected by B. garinii were more likely to have fever, faster-developing and faster-spreading EM lesions and raised levels of CRP and were more likely to be seropositive, all indicating that infections caused by B. garinii are more virulent than those caused by B. afzelii. Our findings are supported by others (7)(8)(9).…”
Section: Clinical Aspects and Laboratory Results According To Genospesupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study the frequency of systemic symptoms was less than reported in the USA, but was similar to other European studies (8,24 infected by B. garinii were more likely to have fever, faster-developing and faster-spreading EM lesions and raised levels of CRP and were more likely to be seropositive, all indicating that infections caused by B. garinii are more virulent than those caused by B. afzelii. Our findings are supported by others (7)(8)(9).…”
Section: Clinical Aspects and Laboratory Results According To Genospesupporting
confidence: 88%
“…In the present study, we found no correlation between appearance and median time from tick bite to diagnosis. Other studies have indicated that B. garinii mostly causes homogeneous EM (8,9) and that different genospecies disseminate with varying intensity, resulting in different symptoms (7,8,10,13,16 with B. afzelii (7). In our study we found that EM caused by B. garinii developed faster and was more likely to be non-annular.…”
Section: Clinical Aspects and Laboratory Results According To Genospesupporting
confidence: 61%
See 2 more Smart Citations
“…The typical primary EM is a ring-shaped or homogeneous erythematous and usually peripherally expanding skin lesion caused by Borrelia burgdorferi sensu lato[1, 2]. In Europe [1,3,4,5,6][] and in the USA [7,8,9], the median or mean maximum diameter of the primary EM varies between 10 and 20 cm with a range of 1–85 cm.…”
Section: Introductionmentioning
confidence: 99%